Legal Protection of Minority Shareholders in the Acquisition of Limited Liability Companies - Walyuddin W (Media Hukum Indonesia (MHI), 2026)
This study examines the legal protection of minority shareholders in the acquisition of Limited Liability Companies based on Law Number 40 of 2007 concerning Limited Liability Companies. The acquisition of a Limited Liability Company, as one form of corporate restructuring, often results in changes in corporate control that may harm the interests of minority shareholders due to the dominance of majority shareholders in the decision-making mechanism through the General Meeting of Shareholders (GMS). This research aims to analyze the extent to which the regulation of company acquisitions under the Company Law is capable of providing legal protection to minority shareholders and to analyze the application of the principles of majority rule and minority protection in the practice of acquisitions of Limited Liability Companies in Indonesia. The research method used is normative juridical research employing statutory and conceptual approaches. The legal materials used consist of primary, secondary, and tertiary legal materials analyzed qualitatively through library research. The results of the study indicate that the Company Law has basically provided legal protection for minority shareholders through various mechanisms, such as appraisal rights, the right to file lawsuits, derivative actions, and the right to obtain protection in the process of acquiring Limited Liability Companies. However, in practice, such legal protection has not been implemented optimally due to the dominance of majority shareholders in the GMS, weak law enforcement, limited access to corporate information, and the absence of strict sanctions against abuses of power by controlling shareholders.